МАСТЕРСТВО ВОСПИТАТЕЛЯ В ПЕДАГОГИЧЕСКОМ ПРОЦЕССЕ - Ботирова, Ш.И. (SCIENCE and SOCIETY, 2022)
This article gives an idea of the knowledge system on the psychological aspects of such issues as pedagogical communication, pedagogical politeness, components of pedagogical abilities, pedagogical skills in the pedagogical process, pedagogical skills in managing the educational process, pedagogical etiquette, pedagogical creativity.